A randomized-controlled trial of low-dose doxycycline for periodontitis in smokers - Ian Needleman (Blackwell Synergy, 2007)
Background/Aim: Tobacco use reduces the effect of non-surgical periodontal therapy. Host-modulation with low-dose doxycycline (LDD) might favour repair and promote an improved treatment response. The aim of this study was to investigate the effect of LDD in smokers on non-surgical periodontal therapy. Material and Methods: This was a parallel arm, randomized, identical placebocontrolled trial with masking of examiner, care-giver, participant and statistician and 6 months of follow-up. Patients received non-surgical therapy and 3 months of test or control drug. Statistical analysis used both conventional methods and multilevel modelling. Results: Eighteen control and 16 test patients completed the study. The velocity of change was statistically greater for the test group for clinical attachment level 0.19 mm/month (95% CI5 0.34, 0.04; p50.012) and probing depth 0.30 mm/ month (95% CI5 0.42, 0.17; po0.001). However, no differences were observed for absolute change in clinical or biochemical markers at 6 months. Conclusions: This study does not provide evidence of a benefit of using LDD as an adjunct to non-surgical periodontal therapy in smokers.